1987
DOI: 10.1148/radiology.162.2.3797641
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial carcinoma staging by MR imaging.

Abstract: The potential of magnetic resonance (MR) imaging in the detection of endometrial carcinoma and in the assessment of its extent was evaluated prospectively in 51 patients clinically suspected of having the disease. MR imaging findings were compared with the results of surgical-pathologic staging and lymph node sampling following hysterectomy. Histologic findings showed 45 patients to have endometrial carcinoma, three to have no residual tumor after dilatation and curettage, and three to have adenomatous hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1
5

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(88 citation statements)
references
References 0 publications
4
78
1
5
Order By: Relevance
“…MRI is a well-established imaging technique for the pre-operative evaluation of endometrial carcinoma [35,36]. However, conventional MRI sequences cannot differentiate between carcinoma, endometrial hyperplasia or benign polyps and histological confirmation is required [35].…”
Section: Discussionmentioning
confidence: 99%
“…MRI is a well-established imaging technique for the pre-operative evaluation of endometrial carcinoma [35,36]. However, conventional MRI sequences cannot differentiate between carcinoma, endometrial hyperplasia or benign polyps and histological confirmation is required [35].…”
Section: Discussionmentioning
confidence: 99%
“…In stage IIA the internal os and the endocervical canal are widened by the hyperintense or inhomogeneous tumor signal at T2-weighted imaging or the hypointense tumor at contrast-enhanced imaging. If the low signal intensity ring of the normal cervical stroma is disrupted, stage IIB can be diagnosed [38,39] (Fig. 4).…”
Section: Criteria For Image Interpretation According To Tumor Stagementioning
confidence: 99%
“…Numerous studies have evaluated the use of MRI to assess the depth of myometrial invasion, and the reported accuracies have ranged from 71% to 97%. 9,10,12,14,22 To the best of our knowledge, a comparative study of the diagnostic accuracy between SH and MRI has not been reported previously. Our results showed that SH had sensitivity of 64.7%, specificity of 87.7%, a PPV of 61.1%, and an NPV of 89.3%, and the diagnostic performance of SH was comparable to that of MRI.…”
Section: Discussionmentioning
confidence: 94%
“…performing and reading SH and MRI was blinded to the results of each imaging modality to minimize the intraobserver bias. Myometrial invasion was defined as a poorly defined interface between the myometrium and endometrium on SH and MRI, and the depth of myometrial invasion was classified into 2 categories according to previously defined criteria 22,23 : (1) invasion of less than half of the myometrium (<50% or superficial) and (2) invasion of half of the myometrium or more (≥50% or deep). The accuracy of SH and MRI in evaluation of myometrial invasion was assessed in comparison with the histopathologic findings (Figures 1 and 2).…”
Section: Methodsmentioning
confidence: 99%